Enhancing Retail Brand Image: A Qualitative Study of Consumer Perception and Return Policy Implementation at PT Sumber Alfaria Trijaya Tbk Bogor Branch - Destia Rahmawati (Manajemen Multitalenta Indonesia, 2026)
The rapid development of the retail industry has intensified competition among companies in delivering high-quality services to consumers. One important aspect of service quality in the retail sector is the implementation of return policies that guarantee consumer rights when products do not meet expectations. Return policies are considered an essential part of after-sales service because they reduce consumer risk and increase trust in the company. This study aims to analyze consumer perceptions and the implementation of return policies in shaping the brand image of PT Sumber Alfaria Trijaya Tbk Bogor Branch. This research employs a qualitative approach with a case study method. Data were collected through interviews, observations, and documentation involving employees responsible for managing return processes. The results indicate that consumer perceptions toward return policies are influenced by the clarity of procedures, ease of the return process, and employee professionalism in handling consumer complaints. Furthermore, the effective implementation of return policies contributes positively to strengthening brand image and increasing consumer trust toward the company. Therefore, return policies not only function as operational procedures but also as strategic tools in improving customer satisfaction and maintaining company reputation in the retail industry.